Is BMI a Valid Indicator of Overweight and Obesity for Adolescents? - Karchynskaya, Viktoryia; Kopcakova, Jaroslava; Klein, Daniel; Gába, Aleš; Madarasova-Geckova, Andrea; van Dijk, Jitse P; de Winter, Andrea F; Reijneveld, Sijmen A (International journal of environmental research and public health, 2020)
Background: Overweight and obesity are mostly monitored via the Body Mass Index (BMI), based on self-reported or measured height and weight. Previous studies have shown that BMI as a measure of obesity can introduce important misclassification problems. The aim of this study was to assess the validity of overweight and obesity classification based on self-reported and on measured height and weight versus the proportion of body fat as the criterion. Methods: We used data on 782 adolescents (mean age = 13.5, 55.8% boys) from the Health Behaviour in School-Aged Children (HBSC) study conducted in 2018 in Slovakia. We obtained self-reported (height and weight) and objective measures (height, weight) and the proportion of fat (as the criterion measure) measured via bioimpedance body composition analysis (BIA) with an InBody 230 from the adolescents. Results: Both measured and self-reported BMI indicated overweight and obesity with relatively low sensitivity (66-82%), but high specificity (90-92%). The superior accuracy of measured BMI in comparison to self-reported BMI was confirmed by the area under the curve (AUC) based on the receiver operating characteristics (ROC) curves (AUC measured/self-reported: 0.94/0.89; p < 0.001). The misclassification of overweight and obesity was significantly higher when using self-reported BMI than when using measured BMI. Conclusion: Both self-reported and measured BMI as indicators of overweight and obesity underestimate the prevalence of adolescents with overweight and obesity.
Keywords: Female; index tělesné hmotnosti; Adolescent; body mass index; overweight; reprodukovatelnost výsledků; mužské pohlaví; Sensitivity and Specificity; nadváha; Obesity; Humans; senzitivita a specificita; tělesná hmotnost; Body Height; adolescents; Slovakia; lidé; Body Weight; obesity; Body Mass Index; Reproducibility of Results; tělesná výška; ženské pohlaví; body fat proportion; Overweight; obezita; Male; mladiství; Slovenská republika